Advances in understanding the predominance, phenotypes, and mechanisms of bacteria related to meat spoilage. (December 2021) - Shao, Liangting; Chen, Shanshan; Wang, Haodong; Zhang, Jinhao; Xu, Xinglian; Wang, Huhu
Abstract: Background: Microbial meat spoilage is responsible for huge losses during production, distribution, and storage of meat products, accounting for approximately 21% of total food losses. A thorough understanding of the characteristics of microorganisms related to meat spoilage is the necessary prerequisite to prevent spoilage processes, and develop innovative preservative approaches and strategies of meat and meat products. Scope and approach: This review has discussed the drawbacks of existing definition of dominant spoilage organisms determining the process of meat spoilage, and the microbial sources of contamination along the specific procedures of meat primary and further processing. Moreover, the spoilage phenotypes of meat and the mechanisms of spoilage bacteria have been highlighted in this review, and the future perspectives, being benefit to break through the current barriers of meat spoilage, have also been covered. Key findings and conclusions: A re-definition of dominant spoilage organisms related to meat spoilage has been concluded, based on the spoilage strength of microbial isolates in situ of meat. The contamination sources are ascribed to the specific processing procedures of chilled meat and meat products, and the microbial biofilm formed on the contact surfaces. Insight into the spoilage determinants including complete genomes of isolates, intracellular metabolic pathways, and exoenzymes secreted by bacteria, could deeply illustrate the molecular mechanisms of microbial spoilage of meat and meat products during storage. Highlights: Meat spoilage causes economic huge losses and numerous food recalls. We review insights into the major microorganisms and sources related to spoilage. We propose a modified two-factor definition of dominant spoilage organisms. We discuss the mechanisms and phenotypes associated with meat spoilage.